2007
DOI: 10.2337/dc06-1128
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in U.S. Adults With Diabetes and At Risk for Developing Diabetes, 2003

Abstract: OBJECTIVE -Given the risk of obesity and diabetes in the U.S., and clear benefit of exercise in disease prevention and management, this study aimed to determine the prevalence of physical activity among adults with and at risk for diabetes.RESEARCH DESIGN AND METHODS -The Medical Expenditure Panel Survey is a nationally representative survey of the U.S. population. In the 2003 survey, 23,283 adults responded when asked about whether they were physically active (moderate or vigorous activity, Ն30 min, three tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
313
5
15

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(358 citation statements)
references
References 35 publications
25
313
5
15
Order By: Relevance
“…This is an alarming finding, as it was previously reported in the United States that especially high-risk subjects do not engage in regular physical activity (Morrato et al, 2007). Therefore, these subjects may be especially prone to dropout en stay in their non-active physical behavior.…”
Section: Dropouts To the Intervention Programmentioning
confidence: 62%
“…This is an alarming finding, as it was previously reported in the United States that especially high-risk subjects do not engage in regular physical activity (Morrato et al, 2007). Therefore, these subjects may be especially prone to dropout en stay in their non-active physical behavior.…”
Section: Dropouts To the Intervention Programmentioning
confidence: 62%
“…However, sustained compliance with exercise programmes, especially by individuals with type 2 diabetes, is at best mediocre [26,27]. Observational studies have revealed associations between the time spent sitting and markers of metabolic disturbance [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…However, most patients with T2D do not meet these standards [19,20]. In fact, people with T2D are less likely to engage in regular PA than their peers without diabetes, even though the majority of people with T2D recognize that regular PA is important [19,20].…”
Section: Introductionmentioning
confidence: 99%